Bad luck and trouble - Child, Lee (London Bantam Books, 2008)
When a man is killed by being thrown from a helicopter high over the California desert, loner Jack Reacher discovers that someone is targeting his old friends and teammates and launches a personal campaign to end the conspiracy before it claims any more lives.
The new Jack Reacher thriller.
Keywords: Reacher, Jack (Fictitious character) -- Fiction; Ex-police officers -- Fiction; Mercenary troops -- Fiction; Middle West -- Fiction